Carcharhinus obscurus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Carcharhinus obscurus (Lesueur, 1818). Dusky Shark. To 4.2 m (13.8 ft) TL (Weigmann 2016). Circumglobal; western Pacific Ocean north to central Japan (Yoshino and Aonuma in Nakabo 2002); Redondo Beach, southern California to Gulf of California (Eschmeyer and Herald 1983); unconfirmed from northern Chile (Ebert et al. 2013). Depth: intertidal to 573 m (1,879 ft) (Hoffmayer et al. 2014). Pazmiño et al. (2019) reported on a number of individuals that were hybrids of C. obscurus and Carcharhinus galapagensis (Snodgrass & Heller, 1905) in the eastern Pacific Ocean. ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 18, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...